Demystifying China’s Fiscal Stimulus - Fardoust, Shahrokh; Lin, Justin Yifu; Luo, Xubei (World Bank, Washington, DC, 2013)
China's government economic stimulus package in 2008-09 appears to have worked well. It seems to have been about the right size, included a number of appropriate components, and was well timed. Its subnational component was designed to maximize the impact of the stimulus package on the economy and minimize the potential procyclical elements that are usually built into subnational fiscal mechanisms in federal countries. Moreover, China's massive fiscal stimulus played an important role in the overall recovery of the global economy. Using a simple analytical framework, this paper focuses on two key factors behind the success of the stimulus: investments in bottleneck-easing infrastructure projects and countercyclical nature of subnational spending based on the assumption that well-chosen infrastructure projects could improve business climate and thereby crowd in the private investment. The paper concludes that the expansionary subnational government spending played a key role in strengthening the overall impact of the stimulus and sustaining growth. It also highlights the importance of public investment quality and cautions about the sustainability of local government financing through the domestic banking system and increases in local governments off balance sheet or contingent liabilities. These lessons may be of particular relevance today for China, as well as other countries, in formulating policy response to another global economic slowdown or crisis, possibly as a result of the Eurozone turmoil. For China, investing in urban infrastructure and green economy, as well as in higher quality and better targeted social services, will be crucial for improving income inequality and inducing a more inclusive growth path.